Identifikasi Segmen Talamau Menggunakan Kombinasi Data Satelit GGMPlus dan Koreksi SRTM2gravity Berdasarkan Analisis Second Vertical Derivative (SVD) - Khairunnisa, Widya Indah; Pohan, Ahmad Fauzi (Jurnal Fisika Unand, 2025)
The existence of the Talamau segment was only identified by the BMKG after the earthquake that occurred on Friday morning 25 February 2022 in Talamau District, West Pasaman Regency. This earthquake had a magnitude of 6.1 Mw with 201 aftershocks. This research aims to determine the characteristics of the fault types of the Talamau segment using the gravity method. The gravity method can describe subsurface geological structures based on differences in rock density known as gravity anomalies. Gravity data is taken from satellite gravity data in the form of GGMplus data and SRTM2gravity topography data. The resulting gravity anomaly value can be used to determine the characteristics of the fault type using Second Vertical Derivative (SVD) analysis. The combination of GGMplus and SRTM2gravity data provides results that can describe the existence of the Talamau segment based on differences in rock density contrast. The existence of the Talamau segment is in a moderate anomalous pattern with the constituent components namely alluvium rock, gravel sand, silt, Talamau mountain rock, inseparable volcanic rock, intrusive rock, and Kuantan formation rock. From the SVD analysis, the characteristics of the fault type of the Talamau segment are also obtained, namely strike-slip faults.